SYSTEM OF SPORTS COMPETITIONS - Mushtariy Razzakova (Journals Park Publishing, 2022)
This material provides analytical information on the activities of the Athlete in the activities of the Sports Competition, which are presented individually, depending on their capabilities.
Keywords: Sports competitions; competition; Competitors